2008
DOI: 10.1200/jco.2007.14.9336
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Clinical and Prognostic Features of Infiltrating Lobular Carcinoma of the Breast: Combined Results of 15 International Breast Cancer Study Group Clinical Trials

Abstract: ILC is more than a histologic variant of breast cancer. The diagnosis of ILC carries distinct prognostic and biologic implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

55
376
5
12

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 406 publications
(448 citation statements)
references
References 32 publications
55
376
5
12
Order By: Relevance
“…those with a triple negative phenotype which underlines the fact that the triple negative is a mixed population of different tumor types, where those without pCR have an extremely poor prognosis [17,18]. A different biological behavior between invasive lobular and invasive ductal breast carcinomas has been described for the adjuvant and neoadjuvant setting [19][20][21]. In our study a total of 277 patients with lobular histology were evaluated and confirmed that this subtype is less sensitive to chemotherapy and will only benefit if other biomarkers defining aggressive behavior as grade 3 or ER/PgR negativity were apparent.…”
Section: Discussionmentioning
confidence: 99%
“…those with a triple negative phenotype which underlines the fact that the triple negative is a mixed population of different tumor types, where those without pCR have an extremely poor prognosis [17,18]. A different biological behavior between invasive lobular and invasive ductal breast carcinomas has been described for the adjuvant and neoadjuvant setting [19][20][21]. In our study a total of 277 patients with lobular histology were evaluated and confirmed that this subtype is less sensitive to chemotherapy and will only benefit if other biomarkers defining aggressive behavior as grade 3 or ER/PgR negativity were apparent.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of ILC carries distinct prognostic and biologic implications. Differences in clinical behaviour between ILCs and invasive ductal carcinomas have been reported [2][3][4][5][6][7]. ILCs have a propensity for multifocal and multicentric distribution but also for bilateralism and a particular pattern of metastatic spread.…”
mentioning
confidence: 99%
“…There are histological subtypes with excellent prognosis: tubular carcinoma, cribriform carcinoma, adenoid-cystic carcinoma, pure mucinous carcinoma [16], as well as subtypes associated with a worse prognosis, frequently diagnosed in a metastatic stage: micropapillary carcinoma, inflammatory carcinoma, NST carcinoma, lobular carcinoma [16,29,30]. Our study revealed that, when present in association with heterogeneous primary tumours, axillary lymph node metastases may present heterogeneous histological types (in 33.33% of cases).…”
Section: Discussionmentioning
confidence: 99%